Sexually transmitted infections and sexual and substance use correlates among young adults in Chiang Mai, Thailand - David D. Celentano (2018)
BACKGROUND: Data on the prevalence of and associated behavioral risk factors for sexually transmitted infections (STI) in young adults in Asia have not been widely studied. STUDY DESIGN: We conducted a cross-sectional study in Chiang Mai, Thailand in 2005-2006 among 658 sexually active participants aged 18 to 25 years, the majority having a history of recent methamphetamine (MA) use. Data were collected by interview and STI were detected using standard laboratory assays. RESULTS: Overall, 38% of participants had at least one laboratory confirmed STI. Herpes simplex virus and Chlamydia were significantly more common among women, whereas hepatitis B virus was significantly more common among men. Men reported a greater number of sexual partners than women, and condom use at last sex was infrequent. Most participants reported using MA at least weekly, with men more frequent users than women, and more often giving reports of frequent drunkenness and lifetime arrests. Behavioral correlates of prevalent STI were similar to the published literature. In multivariate analysis, women ≥20 years of age, with ≥2 heterosexual partners in the past year and a younger age at sexual debut were significantly more likely to have a prevalent STI. Men ≥20 years of age, with ≥2 heterosexual partners in the past year and who enrolled both sex and drug network members were significantly more likely to have a prevalent STI, whereas men who used a condom at last sex were significantly less likely to have a prevalent STI. Substance abuse was associated with behavioral risks but not with prevalent STI. CONCLUSIONS: Sexual risks and substance abuse are substantially elevated among young Thai MA users, but only sexual risks are associated with prevalent STI. © Copyright 2008 American Sexually Transmitted Diseases Association.